2019
DOI: 10.1111/1462-2920.14640
|View full text |Cite
|
Sign up to set email alerts
|

Impact of iron reduction on the metabolism of Clostridium acetobutylicum

Abstract: SummaryIron is essential for most living organisms. In addition, its biogeochemical cycling influences important processes in the geosphere (e.g., the mobilization or immobilization of trace elements and contaminants). The reduction of Fe(III) to Fe(II) can be catalysed microbially, particularly by metal‐respiring bacteria utilizing Fe(III) as a terminal electron acceptor. Furthermore, Gram‐positive fermentative iron reducers are known to reduce Fe(III) by using it as a sink for excess reducing equivalents, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…Several vitamins and ions are essential for solventogenesis and sporulation in Clostridium ( Jamroskovic et al, 2016 ; Nimbalkar et al, 2018 ; Li et al, 2018 ; List et al, 2019 ). These findings contributed to the modification of growth media to improve either the sporulation or the solvent formation.…”
Section: Resultsmentioning
confidence: 99%
“…Several vitamins and ions are essential for solventogenesis and sporulation in Clostridium ( Jamroskovic et al, 2016 ; Nimbalkar et al, 2018 ; Li et al, 2018 ; List et al, 2019 ). These findings contributed to the modification of growth media to improve either the sporulation or the solvent formation.…”
Section: Resultsmentioning
confidence: 99%
“…FIGURE 3 | Example of reduction of resazurin (alamarBlue) into resorufin. (List et al, 2019), maybe through other processes. Furthermore, we can safely assume that resazurin is not likely to be reduced by anaerobes (or during anaerobic respiration, such as sulfate or nitrate reduction), as it is used in media as an oxygen redox indicator.…”
Section: Resazurin (Alamarblue Tm )mentioning
confidence: 99%
“…Previous studies indicated that fermentative bacteria perform Fe(III) reduction by discarding excess reducing equivalents as a form of enhanced fermentation ( Lovley et al, 2004 ; Dalla Vecchia et al, 2014 ). In addition, List et al (2019) suggested that Fe(III) reduction can function as buffer reaction against pH changes in the growth environment, resulting in acidogenesis by fermentation to persist for longer. However, our results showed that the presence of Fe(III) does not critically affect acetogenesis and growth, indicating that the Fe(III) reduction observed in this study is a side reaction for electron transfer not directly linked to energy conservation, as reported in previous studies ( Shah, 2013 ; Dalla Vecchia et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%